Microglia and CD206⁺ border-associated mouse macrophages maintain their embryonic origin during Alzheimer's disease - Wu, Xiaoting (2022)
Brain microglia and border-associated macrophages (BAMs) display distinct spatial, developmental, and phenotypic features. Although at steady state, the origins of distinct brain macrophages are well-documented, the dynamics of their replenishment in neurodegenerative disorders remain elusive, particularly for activated CD11c+ microglia and BAMs. In this study, we conducted a comprehensive fate-mapping analysis of murine microglia and BAMs and their turnover kinetics during Alzheimer's disease (AD) progression. We used a novel inducible AD mouse model to investigate the contribution of bone marrow (BM) cells to the pool of fetal-derived brain macrophages during the development of AD. We demonstrated that microglia remain a remarkably stable embryonic-derived population even during the progression of AD pathology, indicating that neither parenchymal macrophage subpopulation originates from, nor is replenished by, BM-derived cells. At the border-associated brain regions, bona fide CD206+ BAMs are minimally replaced by BM-derived cells, and their turnover rates are not accelerated by AD. In contrast, all other myeloid cells are swiftly replenished by BM progenitors. This information further elucidates the turnover kinetics of these cells not only at steady state, but also in neurodegenerative diseases, which is crucial for identifying potential novel therapeutic targets.